Two-dimensional gel electrophoresis image analysis of two Pseudomonas aeruginosa clones - José Arturo Molina-Mora; Diana Chinchilla-Montero; Carolina Castro-Peña; Fernando García (Tecnología en Marcha, 2022)
A classical strategy to analyse the protein content of a biological sample is the two-dimensional gel electrophoresis (2D-GE). This technique separates proteins by both isoelectric point and molecular weight, and images are taken for subsequent analyses. However, analyses of 2D-GE images require standardized image analysis due to susceptibility of gels to get deformed, presence of overlapping spots and stripes, fuzzy and unstained spots, and others. This represent a difficulty for final users (researchers), which demand for free and user-friendly solutions. We have previously reported the standardization of a protocol to analyse 2D-GE images, and in the current study we applied it to two new bacterial isolates Pseudomonas aeruginosa C25 and C50. We first extracted periplasmic proteins after exposure to antibiotics, and we then run a 2D-GE analysis. Images were analysed using our standardized protocol, achieving the identification of protein spots using CellProfiler after pre-processing step. Comparison between strains was done using differential spot analysis, revealing a specific pattern in the protein expression between bacteria. These results will help to study the biological meaning of these strains using proteomic profiling under different conditions.